Capturing and concentrating adenovirus using magnetic anionic nanobeads - Sakudo A (Dove Medical Press, 2016)
Akikazu Sakudo,1 Koichi Baba,2 Kazuyoshi Ikuta1,31Department of Virology, Research Institute for Microbial Diseases, Osaka University, Yamadaoka, Suita, Osaka, Japan; 2Baba Pediatric Clinic, Kadoma, Osaka, Japan; 3Kanonji Institute, The Research Foundation for Microbial Diseases of Osaka University, Kanonji, Kagawa, JapanAbstract: We recently demonstrated how various enveloped viruses can be efficiently concentrated using magnetic beads coated with an anionic polymer, poly(methyl vinyl ether-maleic anhydrate). However, the exact mechanism of interaction between the virus particles and anionic beads remains unclear. To further investigate whether these magnetic anionic beads specifically bind to the viral envelope, we examined their potential interaction with a nonenveloped virus (adenovirus). The beads were incubated with either adenovirus-infected cell culture medium or nasal aspirates from adenovirus-infected individuals and then separated from the supernatant by applying a magnetic field. After thoroughly washing the beads, adsorption of adenovirus was confirmed by a variety of techniques, including immunochromatography, polymerase chain reaction, Western blotting, and cell culture infection assays. These detection methods positively identified the hexon and penton capsid proteins of adenovirus along with the viral genome on the magnetic beads. Furthermore, various types of adenovirus including Types 5, 6, 11, 19, and 41 were captured using the magnetic bead procedure. Our bead capture method was also found to increase the sensitivity of viral detection. Adenovirus below the detectable limit for immunochromatography was efficiently concentrated using the magnetic bead procedure, allowing the virus to be successfully detected using this methodology. Moreover, these findings clearly demonstrate that a viral envelope is not required for binding to the anionic magnetic beads. Taken together, our results show that this capture procedure increases the sensitivity of detection of adenovirus and would, therefore, be a valuable tool for analyzing both clinical and experimental samples.Keywords: anionic polymer, virus concentration, adenovirus, capture, magnetic beads, poly(methyl vinyl ether-maleic anhydrate)